Pengaruh Pesidual Bendiocarb terhadap Nyamuk Anopheles Aconitus - Bambang Wuryoko Kartika, Sugeng J. Mardihusodo (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Since 1994, mosquito control (An. aconitus) in the malaria control pro-gram in Purworejo regency has changed from fenitrothion 1% insecticide to bendiocarb 80% WP. The insecticide residual effect in the fields (IRS: Indoor Residual Spraying) is very affected by weather condition and the types of wall materials i.e. brick, wood and bamboo. Objective: This study was aimed at elucidating the residual effect of bendiocarb insec-ticides on An. acontius mosquitoes sprayed on different surfaces of wall made of brick, wood and bamboo at the dose of 0,2 g/m2.Methods: Bioassays at the three types of wall surfaces were done every other two weeks for 98 days, with the contact duration for 1 hour and holding periods 24 hours. A random complete block design (RCBD) was applied for the trial. Each treatment on the type of wall surface had 2 replicates and into each biossay cone was introduce 20 adult mosquitoes. Mortality was recorded after 24 hours. The residual effect of the insecti-cide was tested by residual effective time >1 50%. Probit analysis were used to deter-mine the significance difference among the RETs.Results and conclussion: It was concluded that residual effective time of bendiocarb 80% WP were longest on the wooden wall surfaces (until 98th days mortality rate was still 100%), followed by brick (RET50 113 days) and bamboo (RET50 104 days)